2017
DOI: 10.18203/2349-3291.ijcp20173779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of enteric fever in tertiary care hospital of Kashmir

Abstract: Background: Enteric fever is common cause of pyrexia in children and its diagnosis poses several problems, the diagnosis most often remains either as an unsubstantiated clinical impression or a serological diagnosis and occasionally confirmed by blood culture. Typhoid fever is a commonly encountered systemic disease caused by the gram-negative bacteria Salmonella enterica serovar typhi. It is a major public health problem in India. The incidence of enteric fever can be regarded as an index of sanitary measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…No resistance was found to injection ceftriaxone in both the studies [11] . Another study by Sheikh M et al in 2017 found that the blood culture was positive in 27.9%, where Salmonella typhi isolates accounted for 15.5% and Salmonella paratyphi A for 12.4% out of the cohort [12] . On contrary, Jog S et al in their study in 2008, 40% isolates were S paratyphi in blood culture which was reported to be higher than the literature.…”
Section: Discussionmentioning
confidence: 97%
“…No resistance was found to injection ceftriaxone in both the studies [11] . Another study by Sheikh M et al in 2017 found that the blood culture was positive in 27.9%, where Salmonella typhi isolates accounted for 15.5% and Salmonella paratyphi A for 12.4% out of the cohort [12] . On contrary, Jog S et al in their study in 2008, 40% isolates were S paratyphi in blood culture which was reported to be higher than the literature.…”
Section: Discussionmentioning
confidence: 97%
“…Widal was positive in 21/54 (38.8%) patients presenting in the first week of fever, while those presenting in second week or after had positive test in 14/27 (51%) cases. Mushtaq S., et al [14]did Widal test for 129 patients, obtained after mean duration of 4 days in hospital. WIDAL test was considered diagnostic for typhoid fever if titres of more than 1:160 or demonstration of four-fold rise in antibody titre [10].…”
Section: Discussionmentioning
confidence: 99%